New Technologies and Innovation Capacity - Boosting Economic Transition Processes in the Less Favoured Regions - Kati-Jasmin Kosonen (European Regional Science Association (ERSA), 2003)
In the era of knowledge society many regions and local communities/ towns are trying to compete with larger, growing cities over the knowledge and intellectual capital resources. Regional or local knowledge environment has become more important. Building innovation capacity and the institutional capacity as one part of it could be a development tool to some lagging behind-regions, (which are called as less-favoured regions) and quite often do not have universities of their own or successful industries. There are regions, which are building their institutional base by forming university-industry collaborated knowledge transfer institutions and models through networking. Furthermore, these institutions are taking part in the local networks shaping the technological change or transformation in the region. For the beginning there is a need for structures and institutional base strong enough to create critical mass or capabilities. Further there is a need for relationships, which are many times in the forms of networks, between both organisational and non-organisational, formal and informal institutions. Thirdly, the process of institutionalisation is also a crucial element of the development in the less favoured regions (see Healey et al. 1999, Amin & Thrift 1995, Henry 2001). The aim of this paper is to study what kind of collaboration models research and development institutions and actors have formed in the less favoured region for technology transfer and further improving local innovation capacity and technological change. Further the aim is to describe the possible transformation actions appeared in these case regions. The paper is about a process tracking of industrial, technology and innovation development processes in Seinäjoki and Pori town regions. Seinäjoki and Pori sub-regions are the examples of disadvantaged regions in Finland (either peripheral areas or without clear university based education or research), which are building a strong institutional base of higher education (and research) institutions and university-based knowledge transfer systems in order to promote innovations and business development. The category of industrial development to be applied in these cases is a diversification of industries that are already present in the region, from traditional manufacturing to applying new technologies. The studied technology areas are certain parts of automation technology, more particularly intelligent products and systems (mechatronics and applied software). The paper is referred to the Phase I part of "Local Innovation Systems" project led by MIT Industrial Performance Center (10/2001-12/2004). "The Local Innovation Systems"- project is a study about economic transformation of regions/locations and especially the continuing processes that lead to changes over time in the combination of products and services that are produced in that region.
Keywords: 330